2018
DOI: 10.1002/bmc.4251
|View full text |Cite
|
Sign up to set email alerts
|

Development of new extraction method based on liquid–liquid–liquid extraction followed by dispersive liquid–liquid microextraction for extraction of three tricyclic antidepressants in plasma samples

Abstract: In the present study, a new extraction method based on a three-phase system, liquid-liquid-liquid extraction, followed by dispersive liquid-liquid microextraction has been developed and validated for the extraction and preconcentration of three commonly prescribed tricyclic antidepressant drugs - amitriptyline, imipramine, and clomipramine - in human plasma prior to their analysis by gas chromatography-flame ionization detection. The three phases were an aqueous phase (plasma), acetonitrile and n-hexane. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…One of the steps to take into account in an analytical method is the isolation and concentration of analytes of interest from the biological samples under study; the most used procedures for extracting antidepressants are liquid-liquid extraction (LLE) [6,17], solid-phase extraction (SPE) [6,[18][19][20], and some miniaturized techniques-such as solidphase microextraction (SPME) [6,21,22], microextraction by packed sorbent (MEPS) [6,[23][24][25], and dispersive liquid-liquid microextraction (DLLME) [6,[26][27][28][29][30][31]. There are also several methods involving gas chromatography (GC) and liquid chromatography (LC) coupled with mass spectrometry (MS) [26,[30][31][32][33][34][35][36][37][38] or tandem mass spectrometry (MS/MS) [27,[39][40][41][42][43], ultraviolet (UV) [22,28,[44][45][46][47][48], fluorescence [25], diode array (DAD) or photodiode array (PDA)…”
Section: Introductionmentioning
confidence: 99%
“…One of the steps to take into account in an analytical method is the isolation and concentration of analytes of interest from the biological samples under study; the most used procedures for extracting antidepressants are liquid-liquid extraction (LLE) [6,17], solid-phase extraction (SPE) [6,[18][19][20], and some miniaturized techniques-such as solidphase microextraction (SPME) [6,21,22], microextraction by packed sorbent (MEPS) [6,[23][24][25], and dispersive liquid-liquid microextraction (DLLME) [6,[26][27][28][29][30][31]. There are also several methods involving gas chromatography (GC) and liquid chromatography (LC) coupled with mass spectrometry (MS) [26,[30][31][32][33][34][35][36][37][38] or tandem mass spectrometry (MS/MS) [27,[39][40][41][42][43], ultraviolet (UV) [22,28,[44][45][46][47][48], fluorescence [25], diode array (DAD) or photodiode array (PDA)…”
Section: Introductionmentioning
confidence: 99%
“…They reported a sodium valproate concentration in the ranges of 9.9 -34.7 µg mL -1 and 0.5-6.7 µg mL -1 for analyzed patient's plasma and urine samples, respectivly. Farajzadeh et al 130 reported a GC-FID method for determination of amitriptyline, imipramine, and clomipramine in plasma samples after extraction by liquid-liquid-liquid extraction (LLLE) (acetonitrile as extraction solvent, n-hexane as clean up and co-extraction solvent and sodium sulfate as phase separating agent) followed by DLLME method by 1,2-dibromoethane as preconcentration solvent.…”
Section: Gas Chromatography (Gc)mentioning
confidence: 99%
“…Also, DLLME was used for determination of TCAs in biological samples in the previously published papers. 27,[29][30][31][32][33][34][35][36][37][38][39][40][41] Even though, these method removes the main deficiencies of the customary extraction approaches but it also requires toxic organic solvents like chlorinated or aromatic solvents howbeit much less compared to the previous methods. The aim of the present work was to suggest a new and green version of DLLME without using common disperser and extraction solvents.…”
Section: Introductionmentioning
confidence: 99%
“…In the first part, Na 2 SO 4 was added into deionized water (disperser) to prevent the reduction of ionic strength of aqueous sample after injection of the mixture of deionized water and isopropanol into it. To optimize this parameter, various concentrations of Na 2 SO 4 (15-40%, w/v) were added into deionized water, while the other parameters, except isopropanol volume (160, 152, 144, 134, 126, and 120 μL of isopropanol for15,20,25,30,35, and 40 % w/v, of Na 2 SO 4 , respectively) were kept constant during the microextraction procedure.…”
mentioning
confidence: 99%